Factors Contributing to Persistent Frequent Attendance in Primary Care Among the Oldest Old: Longitudinal Evidence From the AgeCoDe-AgeQualiDe Study - Buczak-Stec, Elżbieta W.; Hajek, André; van den Bussche, Hendrik; Eisele, Marion; Oey, Anke; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; Pentzek, Michael; Luppa, Melanie; Löbner, Margit; et al. (Frontiers in Medicine, 2022)
Objective: Since there is a lack of longitudinal studies in this area, our aim was identify the determinants of persistent frequent attendance in primary care among the oldest old in Germany. Methods: Longitudinal data (follow-up wave 7 to 9) were taken from the multicenter prospective cohort “Study on Needs, health service use, costs and health-related quality of life in a large sample of oldest-old primary care patients (85+)” (AgeQualiDe), covering primary care patients ≥ 85 years (FU7 n = 741, mean age 88.9 years (SD 2.9; 85-100)). Persistent frequent attenders of GP services (the patients in the top decile of the number of GP consultations in two or more consecutive waves) was our main outcome of interest. Logistic random-effects models were used. Results: Our analysis included 1,891 observations (766 individuals). Across three waves we identified 56 persistent frequent attenders. Results of random-effects logistic regressions showed that odds of being persistent frequent attender were higher for widowed individuals (OR=4.57; 95% CI [1.07-19.45]). Moreover, a one-point increase in the frailty score and having one more chronic condition increased the odds of being persistent frequent attender by 68% (OR =1.68; 95% CI [1.05-2.69]) and 23% (OR=1.23, 95% CI [1.05-1.44]), respectively. Conclusion: Our study stressed the longitudinal association between frailty, widowhood as well as chronic diseases and persistent frequent attendance among the oldest old in Germany.